Microplastics risk at the interface of circular economy, quality and food safety in Poland: a case study - Piotr Kafel (Vilnius Gediminas Technical University, 2021)
The purpose of this paper is to explore the scope of undertaken and planned actions related to microplastics risk in one of the biggest polish food sector company for better understanding the relations between quality management, food safety management and circular economy. To explore the planed and undertaken actions in relation to microplastics risk a case study was performed. It was performed in one of the leading polish organization producing and selling food products of an international range of operation. During the study representative of the leadership of the organization was interviewed as well as relevant instructions and records provided by the organization were analysed. Results indicate that the issue of microplastics for studied company is a marginal problem, that has not been given much attention so far. On the other hand, significant changes at the global level such as circular economy strategy lead to changes in the design of products (mainly packaging). To the best of the authors’ knowledge, this is the first study to examine the microplastics risk from the perspective of the management systems implemented in food sector organization with the circular economy context. This study enriches current knowledge about circular economy and its integration with other management systems in the microplastics elimination context.